Research Budget Improves National Product Independence: A National Resilience Perspective - Sri Cahyo Kasihono; Suwito , Suwito (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The current fundamental problem is the low national research budget, as well as the lack of domestic product innovation so that it will have an impact on the lack of innovation in creating the latest products and defense technology that is still unable to be produced domestically and requires imports of raw materials. This will be potentially bad for a country's national resilience with the country's dependence on foreign products, which will pose a vital risk to the survival and resilience of the nation in the face of crisis. National resilience as the ability of a country to protect its welfare, identity, and political integrity actual and potential threats. There are several elements in the form of ideological, political, social, economic and military. The purpose of this study is to analyze the potential of the research budget in increasing the independence of national products and formulate recommendations in optimizing government policy. This research uses a qualitative descriptive method with a literature study approach, collecting secondary data sourced from official reports, journal articles, and government publications related to the topic of this research. Analysis is conducted on the current condition of imported product dependence and domestic product innovation capacity, when looking at opportunities and challenges in increasing national product independence. The results of this study show the potential of the research budget. If the research budget is increased in order to make the latest innovations and produce domestic strategic products, in order to increase the independence of national products, there is great potential for innovation and encourages the acceleration of the latest strategic innovations in domestic products. So that it can be expected to be a reference for the government in increasing the independence of national products so as to reduce dependence on imported products.